2014
DOI: 10.1155/2014/135357
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of VEGF in Patients Submitted to Percutaneous Coronary Intervention

Abstract: We examined the longitudinal changes of VEGF levels after percutaneous coronary intervention for predicting major adverse cardiac events (MACE) in coronary artery disease (CAD) patients. VEGF was measured in 94 CAD patients' serum before revascularization, 1-month and 1-year after. Independently of clinical presentation, patients had lower VEGF concentration than a cohort of healthy subjects (median, IQ: 15.9, 9.0–264 pg/mL versus 419, 212–758 pg/mL; P < 0.001) at baseline. VEGF increased to 1-month (median, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
3
17
1
3
Order By: Relevance
“…38 Circulating levels of VEGF could affect the outcome of AMI. 20,38,39 We have previously reported depressed serum VEGF concentrations immediately after AMI which increase over 1 year, 20 with a similar trend to that observed in this study for sCD40L. The association between sCD40L and circulating VEGF was also described by Lim et al 40 in CAD patients; however, in this case, the levels of both markers were increased in those patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…38 Circulating levels of VEGF could affect the outcome of AMI. 20,38,39 We have previously reported depressed serum VEGF concentrations immediately after AMI which increase over 1 year, 20 with a similar trend to that observed in this study for sCD40L. The association between sCD40L and circulating VEGF was also described by Lim et al 40 in CAD patients; however, in this case, the levels of both markers were increased in those patients.…”
Section: Discussionsupporting
confidence: 88%
“…[17][18][19] The prognostic information provided by VEGF independently of other markers likely points toward an important role for angiogenesis in regulating myocardial repair and reperfusion after AMI. 17,20 Current opinion suggests a differential role of CD40L (both soluble and membrane-bound forms, which includes microparticles in circulation) 21 at different stages of CAD, contrasting with the traditional view of an unvarying function of the CD40L-CD40-sCD40L system interactions in the disease. 6 In that perspective, no clear indication of the interplay of CD40L with endothelial and vascular function markers and their importance in the pathophysiology of the AMI has been obtained so far in human clinical studies.…”
mentioning
confidence: 94%
“…In most clinical studies, an increase in the VEGF-A level in AMI compared to healthy persons, patients with stable or unstable angina [8, [19][20][21][22][23][24] was determined. At the same time, in works by Ramos et al [17], the level of VEGF-A in patients with CAD was lower than in healthy persons, and its differences between clinical forms of coronary heart disease were not found.…”
Section: Introductionmentioning
confidence: 88%
“…Information on changes in the VEGF-A level with stable CAD compared to the healthy group varied from its increase [14][15][16], to decrease [17] or lack of changes [18]. A number of studies have shown a direct correlation between the level of VEGF-A growth and the degree of damage to coronary vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation